Preparation of Tea Tree Oil Microcapsules and Their Effects on Strawberry Preservation During Storage - Yan-Li Han; Cen Chen; Yuan-Yue Wu; Yu-Meng Yan; Meng-Ying Wang; Yang Xiang; Dao-Yu Wei; Zhi-Hang Hu; Jing Zhuang; Ai-Sheng Xiong; Yuan-Hua Wang (Horticulturae)
This study used an embedding technique to prepare microcapsules with tea tree oil as the core material and a composite of β-cyclodextrin and nano-montmorillonite as the wall material. The prepared microcapsules were analyzed for their morphological characteristics, thermal stability, and major components. Additionally, the microcapsules’ effect on the quality of and active substances contained in refrigerated strawberries was investigated. The results revealed that the optimal preparation conditions for the microcapsules were a montmorillonite addition of 2% (m/v), a core-to-wall ratio of 1:12 (m/m), an encapsulation temperature of 70 °C, and an encapsulation time of 90 min. Under these conditions, the microcapsules achieved an encapsulation efficiency of 77.67%. The capsules emitted a noticeable aroma of tea tree oil, and their primary components, specifically terpinen-4-ol, 1,8-cineole, p-cymene, and terpinolene, were consistent with those of tea tree oil. The release rate of the microcapsules at 60 °C and 90 °C was significantly lower than that of liquid tea tree oil (p < 0.05). A suitable treatment with tea tree oil microcapsules preserved the appearance and quality of the strawberries, inhibited spoilage during refrigeration, reduced weight loss, maintained firmness, delayed declines in soluble solid contents and acidity in later storage stages, and enhanced the activity of the superoxide dismutase, catalase, and ascorbate peroxidase. The prepared microcapsules also suppressed increases in anthocyanins and inhibited the further maturation of the stored strawberries. The optimal preservative effect was achieved with the placement of 5.0 g of tea tree oil microcapsules per 1.2 L of storage space.